2006
DOI: 10.1111/j.1742-7843.2006.pto_535.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Lignophenol Derivative from Beech (Fagus crenata Blume) on Copper‐ and Zinc‐Mediated Cell Death in PC12 Cells

Abstract: Lignophenol, prepared using a phase-separation system, is a derivative of lignin, which is one of the components in the plant cell wall, and possesses high phenolic function, high stability and antioxidant properties. However, little is known about the beneficial effect of lignophenol. In this study, we investigated the protective effect of lignophenol from the beech tree (Fagus crenata Blume) on copper-and zinc-mediated apoptosis in PC12 cells by using DNA fragmentation and TUNEL assays. In DNA fragmentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In addition, lignocresol, a derivative from bamboo, demonstrated anti-apoptotic effects against hydrogen peroxide in human neuroblastoma cells in which caspase-3 activation was inhibited (Akao et al, 2004). 2-Methxoy-p-cresol is generally believed to be the anti-apoptotic constituent of pyrolyzates, and lignophenol is a p-cresol derivative that exhibits high phenolic function and antioxidant properties in vitro (Sato et al, 2006). It has been assumed that pyrolyzates may reduce neuronal damage by blocking Ca 2+ influx via NMDA receptors, or inhibiting apoptotic factors such as hydrogen peroxide.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, lignocresol, a derivative from bamboo, demonstrated anti-apoptotic effects against hydrogen peroxide in human neuroblastoma cells in which caspase-3 activation was inhibited (Akao et al, 2004). 2-Methxoy-p-cresol is generally believed to be the anti-apoptotic constituent of pyrolyzates, and lignophenol is a p-cresol derivative that exhibits high phenolic function and antioxidant properties in vitro (Sato et al, 2006). It has been assumed that pyrolyzates may reduce neuronal damage by blocking Ca 2+ influx via NMDA receptors, or inhibiting apoptotic factors such as hydrogen peroxide.…”
Section: Discussionmentioning
confidence: 98%
“…Similar results were obtained by many other researchers. Sato et al (2006) found that LPs had an anti-apoptotic effect on pheochromocytoma (PC12) cells treated with an excessive amount of Cu and Zn, which were highly associated with ROS generation and oxidative cell injury.…”
Section: Lignin-based Polymers/lignophenolsmentioning
confidence: 99%
“…Lignophenols (LPs) are lignin-derived macromolecules produced experimentally from raw biomass by phase-separation systems, in which cellulose and hemicellulose of lignocellulosic are converted into hydrolyzed carbohydrates while lignin is converted into LPs (Sato et al, 2006;Lochab et al, 2014). Under hydrothermal conditions, these lignin-based polymers can be further converted into monophenols (e.g., phenol, catechol, syringol, and cresol) (Lochab et al, 2014).…”
Section: Lignin-based Polymers/lignophenolsmentioning
confidence: 99%
“…Recently, an LPs from bamboo has been reported to prevent hydrogen peroxide‐induced cell death in vitro [5]. We have also reported the protective effect of LPs from Beech ( Fagus crenata Blume) on copper‐ and zinc‐mediated cell death in rat pheochromocytoma (PC12) cells [6]. However, to the best of our knowledge, no previous study has examined the physiological effects of LPs on lipid metabolism.…”
mentioning
confidence: 99%